2017
DOI: 10.12688/gatesopenres.12750.1
|View full text |Cite
|
Sign up to set email alerts
|

Using biomarkers to predict TB treatment duration (Predict TB): a prospective, randomized, noninferiority, treatment shortening clinical trial

Abstract: Background: By the early 1980s, tuberculosis treatment was shortened from 24 to 6 months, maintaining relapse rates of 1-2%. Subsequent trials attempting shorter durations have failed, with 4-month arms consistently having relapse rates of 15-20%. One trial shortened treatment only among those without baseline cavity on chest x-ray and whose month 2 sputum culture converted to negative. The 4-month arm relapse rate decreased to 7% but was still significantly worse than the 6-month arm (1.6%, P<0.01).  We hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The two manual readers are clinicians, with experience in the diagnosis and treatment of pulmonary tuberculosis. They are also clinical trial investigators and trained in PET-CT evaluation for a phase 3 clinical trial that aims to use PET-CT parameters to guide TB treatment duration [ 28 ]. Manual segmentation of FDG-avid PET lesions in PTB scans took roughly 30–90 min per scan.…”
Section: Methodsmentioning
confidence: 99%
“…The two manual readers are clinicians, with experience in the diagnosis and treatment of pulmonary tuberculosis. They are also clinical trial investigators and trained in PET-CT evaluation for a phase 3 clinical trial that aims to use PET-CT parameters to guide TB treatment duration [ 28 ]. Manual segmentation of FDG-avid PET lesions in PTB scans took roughly 30–90 min per scan.…”
Section: Methodsmentioning
confidence: 99%
“…In related publications, these quantitative metrics also correlate well with host biomarkers, namely gene expression signatures [46], and urinary concentration of the recently discovered metabolite, serylleucine core 1 O-glycosylated peptide [50]. The potential of quantitative FDG PET-CT variables to identify patients with a low risk of treatment failure was also analysed in combination with other patient variables and is currently being tested in the PredictTB trial [51].…”
Section: Comparison With Previous Literaturementioning
confidence: 96%
“…Multiple enrollment sites will be required to provide the statistical power for comparing alternative therapeutic strategies, given the smaller number of NTM lung disease patients compared with tuberculosis on a global scale. Furthermore, clinical studies supported by the National Institutes of Health ( Sigal et al, 2017 ) and the Bill & Melinda Gates Foundation ( Chen et al, 2017 ) have demonstrated the feasibility of integrating biomarker assessment into clinical trial design.…”
Section: Future Directionsmentioning
confidence: 99%